2014
DOI: 10.1007/s12088-014-0450-3
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Acetic Acid on the Xylose Utilization and Bacterial Cellulose Production by Gluconacetobacter xylinus

Abstract: In this work,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…In our previous study, acetic acid has been proved to be one carbon source that could stimulate BC accumulation (Yang et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In our previous study, acetic acid has been proved to be one carbon source that could stimulate BC accumulation (Yang et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, after the 6th day, the consumption of organic acids by G. xylinus became faster. In our previous study, acetic acid has been proved to be one carbon source that could stimulate BC accumulation (Yang et al 2014).…”
Section: Metabolism Of Gluconacetobacter Xylinus In Abe Fermentation mentioning
confidence: 99%
“…In our study, all used carbon sources were sugars except for acetate and ethanol, which are well-known substrates responsible for enhancing ATP production and inhibiting the anti-BC production processes [17]. The studies focusing on acetate and (or) ethanol addition and their consequent effects on BC production have been well documented [17,18,19,20]. Although some studies have tried to produce BC using acetate or ethanol as a sole carbon source, the BC yields are much lower than for sugars [16,36].…”
Section: Resultsmentioning
confidence: 99%
“…More often, both ethanol and acetate are spiked in media to enhance BC production by improving adenosine triphosphate (ATP) production, which is responsible for energy supply in the tricarboxylic acid (TCA) cycle and sugar metabolisms. Specifically, these processes are achieved by promoting the activities of glucokinase and fructokinase for BC production and inhibiting the activities of gluconokinase and glucose-6-phosphate dehydrogenase in pentose phosphate metabolism for energy production [17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason for the increase could be the addition of acetic acid that was used for dissolving chitosan, which could be utilized as a carbon source for G. xylinus . Previous studies have shown that acetic acid can enhance BNC yield (Yang et al, 2014 ). However, the cellulose production was much lower after adding chitosan than that in the chitosan-free culture medium (1.46 g/L), indicating a serious inhibiting effect on cellulose production under static culture condition.…”
Section: Resultsmentioning
confidence: 97%